Mulheres empoderadas - uma experiência de gestão no sertão nordestino - Brandão, Tatiana Frey Biehl (Universidade Federal de São Carlos, 2016)
The study area of this work is the Alto Sertão of Sergipe, considered to be one of the most rural territories in the Northeast of Brazil. In this setting, there is the target audience of this research, mainly composed by family agriculturists who integrate the Association of Women „Resgatando Sua História‟ and work with different agricultural and non-agricultural activities, following the agroecology guidelines. This way, it is possible to notice the need of agriculurists to know the management tools to administrate the diversified range of information inherent to local productive, ecological and economical resources. So, this work has as its objective verifying what are the accounting-financial management instruments adopted by the Association, and also observing the socialproductive system to see if it is an alternative to improve their life conditions. We chose a qualitative approach to conduct this study, and data collection was performed through direct observations and semi-structured interviews with the associates. It was observed that they appropriated the necessary accounting and financial knowledge, so they could play the main role on the development of the agricultural and para-agricultural, management and social representation activities. We concluded that their organization as an association and acting under the precepts or agroecology has collaborated on the autonomy and empowering of women by increasing their income, food and nutrition security and ecological conservation of the caatinga, social-productive and political insertion of the associates. Also, data transparency of economical and financial data of the Association has collaborated to continue this solidary enterprise.
Women empowered - a management experience in the northeast sertão
Keywords: Empoderamento das mulheres; Associativismo; Agroecologia no semiárido; Gestão; Instrumentos contábeis-financeiros; Women‟s empowering; Associativism; Agroecology in semiarid; Management; Accounting-financial instruments; CIENCIAS AGRARIAS